1996
DOI: 10.1164/ajrccm.153.1.8542155
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal capsaicin treatment increases the severity of ozone-induced lung injury.

Abstract: To test the hypothesis that lung sensory C fibers protect the small distal airways and alveoli from oxidant injury, we compared the effects of inhalation of ozone (1 ppm) or filtered air for 8 h on lung injury and lung inflammation in four groups of rats: (1) normal rats exposed to filtered air; (2) normal rats exposed to ozone; (3) rats treated as neonates with capsaicin (50 mg/kg, intraperitoneally) and subsequently exposed to filtered air; and (4) rats treated as neonates with capsaicin and subsequently exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
27
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 24 publications
7
27
1
Order By: Relevance
“…There was no significant difference in the number of neutrophils in BAL or in terminal bronchioles of rats treated with SR140333 compared with vehicle-treated rats exposed to ozone. These observations are consistent with our previous observations in rats treated neonatally with capsaicin to ablate C fiber afferents (26). Taken together, these results suggest that substance P is not a critical mediator for neutrophil emigration into airways after ozone injury in the rat.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…There was no significant difference in the number of neutrophils in BAL or in terminal bronchioles of rats treated with SR140333 compared with vehicle-treated rats exposed to ozone. These observations are consistent with our previous observations in rats treated neonatally with capsaicin to ablate C fiber afferents (26). Taken together, these results suggest that substance P is not a critical mediator for neutrophil emigration into airways after ozone injury in the rat.…”
Section: Discussionsupporting
confidence: 93%
“…In a series of experiments, we found that rats depleted of C fibers with neonatal capsaicin treatment did not develop reflex rapid, shallow breathing, epithelial injury of terminal bronchioles was greater, and there was an uncoupling of neutrophil accumulation and other inflammatory responses from repair after ozone exposure. That is, for a given amount of epithelial necrosis, C fiber ablation had no influence on the degree of inflammation, but did modulate epithelial cell turnover and proliferative repair (26,27). Although clearly implicating airway C fibers and the neuropeptides they release in ozoneinduced epithelial injury and repair, interpretation of these observations are complicated by the fact that we do not know how the neonatal ablation of airway C fibers with capsaicin affects the ontogeny of the distal airway epithelium and its response to oxidant stress.…”
mentioning
confidence: 96%
“…controlled inflammatory responses 22,23 . Furthermore, in humans, low levels of soluble L-selectin (that is, minimal shedding) in the early course of disease are negatively correlated with degree of organ injury in adult respiratory distress syndrome 24 .…”
Section: Articlesmentioning
confidence: 99%
“…In a series of experiments, we found that rats depleted of C fibers using neonatal capsaicin treatment did not develop rapid shallow breathing, epithelial injury of terminal bronchioles was greater, and there were reductions in epithelial cell turnover and proliferative repair (Sterner-Kock et al 1996;.…”
Section: Introductionmentioning
confidence: 99%